When time slows down: temporal distortion and addictive social media use - Vinci, Leonarda Anna; Savioni, Lucrezia; Triberti, Stefano (Frontiers in Psychology, 2025)
This article represents a theoretical contribution on the involvement factors involved in temporal processing related to the use of social media networking. Current literature agrees in highlighting that individuals are not very accurate in making temporal judgments with respect to the duration and progression of events, since they often tend to perceive time in an accelerated or slowed way. The temporal distortion between real time intervals and subjective perceived ones involves several cognitive and emotional biases, implicated in the modalities and frequency of use of social media. These factors, associated with particular individual predispositions, can favor the development of a problematic use of social media in terms of temporal planning and overlapping of activities. This work discusses a possible cyclical model that broadens the understanding and emphasizes the central role of temporal distortion in the onset of social media addiction.